The Factors Associated With Menstrual Disorder In Female Students Of The Institute Of Home Affairs Governance - Rahma Amalyah; Rosita, Rosita; Yanti Herawati; Sri Hennyati A (Jurnal EduHealth, 2024)
World Health Organization (WHO) 2020 report, the prevalence of menstrual cycle disorders in women is around 45%. Basic Health Research data (2018), explains that in Indonesia, women aged 10-59 years experience irregular menstrual problems as much as 13.7% in 1 year. A preliminary survey conducted by researchers on 22 female students at Institute of Home Affairs Governance found that female students who experienced dysmenorrhea were 50%, menstrual cycle disorders (polymenorrhea, oligomenorrhea and amenorrhea) were 22.72%, premenstrual syndrome was 22.72% and hypermenorrhea was 4.5%. Purpose of the study is to determine the factors associated with menstrual disorders in female students at the Institute of Home Affairs Governance. Research method is analytical research with a cross sectional time approach. The sampling technique used total sampling which amounted to 171 adolescent girls. The results of statistical tests using the Chi Square test and the alternative test of fisher freeman halton test showed there was a relationship between stress levels and menstrual disorders with a p-value of 0.04. There was no relationship between nutritional status and physical activity with menstrual disorders with p-value 0.22 and 0.48. There is a significant correlated between stress levels and menstrual disorder on female student at  Institute of Home Affairs Governance.